A Review on Economic Benefits and Impact of Biosimilars on Healthcare System: Review Article (Journal of Pharma Insights and Research, 2025)
Biologics hold a significant portion of global pharmaceutical expenditure, accounting for 43% of drug costs while constituting only 2% of prescriptions in developed markets. The usage of biosimilars in healthcare systems has emerged as a crucial strategy for cost containment and improved treatment accessibility. Biosimilars show comparable safety and efficacy profiles to reference biologics, have achieved price reductions of 20-70% across various therapeutic areas. The European Union leads in biosimilar adoption, with penetration rates reaching 90% in specific therapeutic categories, while the United States market projects savings of $133 billion by 2025. Developing nations, particularly India and South Korea, have established robust biosimilar manufacturing capabilities, enhancing global access to biological therapies. However, multiple barriers impede optimal biosimilar utilization, including regulatory complexities, patent litigation, and healthcare provider hesitancy. Implementation of streamlined approval pathways, physician education programs, and value-based procurement strategies has demonstrated success in overcoming these challenges. By 2030, projected global biosimilar savings may exceed $290 billion, particularly benefiting therapeutic areas such as oncology, rheumatology, and endocrinology. The economic advantages of biosimilars extend beyond direct cost savings, enabling healthcare systems to reallocate resources, expand treatment access, and maintain long-term sustainability.